Ethnicity influences total serum vitamin B12 concentration: a study of Black, Asian and White patients in a primary care setting. Issue 9 (5th May 2021) - O'Logbon, Jessica; Crook, Martin; Steed, David; Harrington, Dominic Jon; Sobczyńska-Malefora, Agata
Abstract : Aims: A growing body of evidence suggests that ethnicity and race influence vitamin B12 metabolism and status yet clinical awareness of this is poor, causing doubts regarding diagnosis and treatment. Moreover, deficiency and insufficiency cut-offs are universally applied for this test in most diagnostic settings. The objective of this study was to assess serum vitamin B12 concentrations in Black, Asian and White primary care patients in London, UK, particularly in patients of Black or Black British ethnic origin and establish if there is a need for specific reference ranges. Methods: Serum B12 results from 49 414 patients were processed between January 2018 and November 2019 using the Architect assay (Abbott Diagnostics) at St. Thomas' Hospital, London, UK. Age, sex and ethnicity data were collected from the laboratory Health Informatics Team. Results: Black patients (n=13 806) were found to have significantly higher serum vitamin B12 concentration across all age groups and both sexes, especially Nigerian patients (median B12 505 pmol/L, IQR: 362–727, n=891), compared with Asian and White ethnic groups (p<0.001). Binary logistic regression analysis revealed that the Black or Black British ethnic group had the strongest association with elevated serum B12 (>652 pmol/L) (adjusted OR 3.38, 95% CI 3.17 to 3.61, p<0.0001). Conclusions: It is likely that a combination of genetic and acquired/environmental factors are responsible for the ethnic differences in serum B12 . This suggests that there is a need for ethnic-specific reference ranges with indications for the incorporation of age and sex too.